If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x2-4x+5=10
We move all terms to the left:
x2-4x+5-(10)=0
We add all the numbers together, and all the variables
x^2-4x-5=0
a = 1; b = -4; c = -5;
Δ = b2-4ac
Δ = -42-4·1·(-5)
Δ = 36
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$\sqrt{\Delta}=\sqrt{36}=6$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-4)-6}{2*1}=\frac{-2}{2} =-1 $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-4)+6}{2*1}=\frac{10}{2} =5 $
| v/10-35/10=0 | | 35=2u+13 | | 4t^2+12t+5=0 | | v-35/10=0 | | x2+3=9 | | -456=-8(1-8p) | | (2/3x)-(-3/2x)=0 | | -7+7p=1+8p | | 7y-27=2(y+9) | | -2x+26=2 | | -9/5+8/5=-1/2x+3 | | 7y-27=2(y+9 | | 5u-25=2(u-5) | | x2+14x+49=9 | | 0.5x-3=13 | | 2x2+10=60 | | x+2x/3+x/2+x/7=33 | | x+15=1/2(30+(9x-42)) | | 33=x=58 | | 3(-x+9)=8-6x | | 3x+2x+5=8x-13 | | 20=6y+8 | | x+(x+5)+2(x+5)=35 | | 4x+(3x+1)=6-2(x-1) | | 6+-3m=15 | | 30=2(u+6)-5 | | 7x+6=x+6 | | -6=-8w+5(w-3) | | 10x+4=8x+24 | | 4a=4-20 | | 10x5=20-20x | | w+14=√256 |